Neovascular events in eyes with central retinal vein occlusion undergoing serial bevacizumab or ranibizumab intravitreal injections: A retrospective review - Francis Char DeCroos; Bozho Todorich; Rayan Alshareef; Mohammed Khuthaila; Sharon Fekrat; Allen C Ho; Carl D Regillo; Marc J Spirn (Journal of Ophthalmic & Vision Research, 2014)
Purpose: To characterize the onset and type of neovascular events in eyes with central retinal vein occlusion (CRVO) undergoing serial anti-VEGF therapy. Methods: Consecutive eyes undergoing serial intravitreal bevacizumab or ranibizumab injections for treatment of CME secondary to CRVO were identified. Pertinent data was retrospectively collected and included type and onset of the neovascular event, and the treatment free interval from last injection until the neovascular event. Kaplan-Meier life table analysis was performed to determine the differential effects of baseline perfusion status, early initiation of anti-VEGF treatment (within 3 months of CRVO onset) versus later treatment, and continuous (1-month±2 weeks) versus discontinuous treatment interval (>1.5 months) on time until neovascular event. Results: Of 31 eligible eyes, 12 (39%) and 19 (61%) presented with perfused and ischemic CRVO, respectively. The mean duration from CRVO until the onset of any neovascular event was 17.0±10.3 months. The mean treatment-free interval prior to any neovascular event was 6.2±7.3 months. On average, 5.3±3.2 anti-VEGF injections were given prior to any neovascular event. Neovascularization of the iris or angle occurred in 18 eyes (58%), vitreous hemorrhage associated with neovascularization was observed in 9 eyes (29%) and neovascularization of the disc developed in 5 eyes (16%). Neovascular events showed a trend towards occurring later in eyes with perfused CRVO at baseline (log rank test, P=0.07). Conclusion: Neovascular events occur in eyes with CRVO undergoing serial anti-VEGF therapy, and these events may be delayed compared to the natural history of CRVO-associated neovascularization. Iris neovascularization occurred most frequently.